Three security challenges for Lithuania - Goble, Paul A. (Politologija, 1998)
For the very concern of Lithuanian politicians, politologists, and security analysts, Paul A. Goble, Radio Free Europe/Radio Liberty, discusses one of the most pertaining problems in Lithuania today, namely, the dilemma of national security and the challenges to it. With respect to the former, the author analyses 'three security challenges for Lithuania': one from the East, a second from the West, and a third from inside the country itself. The author claims that unless Lithuanians and their friends both recognize the nature of each and the ways in which they are interrelated, understand both the opportunities and limitations of Lithuania's position at the present time, and work to deal with them both individually and collectively, Lithuania is certain to suffer in ways that "no friend of that country could want to see." Therefore, the main task of the author is to provide for a detailed examination of the nature of the problems in order to help develop a strategy to overcome them. First, in three opening sections, the author discusses the nature of each of the problems (challenges), its present status, and the influence (repercussions) on Lithuania's security. Thus, in the last section, he offers a five-part strategy that could help overcome these problems.In the first section of the work, "An Incomplete Acceptance," P. Goble emphasizes the failure of the Russian government and the Russian people to fully accept the events of 1990-1991 in Lithuania. He says that in spite of the grandiose plans of Russia in regard to the Baltics (both the official policy of Moscow and, for example, a recent statement on "Russia and the Baltics" released by the Moscow-based Centre for Security and Defence Policy is held in mind), it has no power to implement them. However, such weaknesses, the author postulates, divisions amongst Russian politicians, have so far had three negative influences on Lithuania itself: first, it has kept Lithuanian political elite off balance with each side able to point to something that Russia supposedly is doing or not doing; second, it has allowed Moscow to gain influence without having to spend much in the way of resources; and third, it has detracted Lithuanian attention from the ways in which Russian political forces are actually behaving with respect to Lithuania, undermining certain institutions, including banks and other firms. Thus, the author proceeds to describe "this anything, but clear" Russian policy towards Lithuania in outline. Three viewpoints on the political behaviour of Russia are presented.In the second section of the text, "A Changed West," the author argues that "the West has changed even more than the East in terms of Lithuania's security interests." In this rather critical manner, he presents three viewpoints: first, for the Western countries good relations with Moscow have taken precedence over good relations with the West's former allies, including Lithuania, against the Soviet Union. Therefore, countries of Central-Eastern Europe, Lithuania among them, which are not as large and do not have nuclear warheads, are left adrift; second, the West has decided to enlarge NATO and the EU. However, the process is of dubious value - it is not clear whether the new institutions correspond to the changed circumstances; and third, the author argues that in the absence of a direct and immediate threat to itself, the West has failed to provide the kind and level of assistance needed to cope with the new situation, namely, failure to provide assistance for coping with organized crime and the weakness of civil society.In the third section, the author enumerates three "real" problems of Lithuania itself: first, many Lithuanians assumed that having recovered their political independence, everything else would come naturally and easily; second, many Lithuanians thought that the new "big brother," the West, would come and solve the problems for them; and third, many Lithuanians thought that Lithuania might immediately restore its advantageous position in the world. He gives us quite a critical review of what kind of problems and failures exist, what is the real, changed, and nowadays, situation, saying that "political independence has definitely proved to be less than enough."In the final section, "A Disciplined Approach to the Future," P. A. Goble advises upon what Lithuania should do. He suggests a five-part strategy that addresses all of these challenges at once, viz.: first, Lithuania must pursue an inclusive ("both/and") rather than ("yes/no") approach to international affairs. In addition to striving to become part of the Western institutions, NATO and the EU, Lithuania should seek to improve its relations with Russia; second, although to the detriment of Baltic unity, Lithuania must develop as a regional actor, closely allied with Poland and the other Central European states; third, Lithuania must continue to expand its ties with the United States; fourth, Lithuania must recognize that in the post-cold war environment, NATO and the EU will not save Lithuania; fifth, Lithuania must get busy working on building the institutions of a civil society. The author believes that, if this strategy is implemented, Lithuania can resume her place in Europe.
Keywords: -